2021
DOI: 10.1080/17457289.2021.1924752
|View full text |Cite
|
Sign up to set email alerts
|

Down with Covid: patterns of electoral turnout in the 2020 French local elections

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…Interest in politics and occupation also play here a stronger role than in the first round. As suggested by Haute and colleagues ( 2021 ), the pandemic context may have reinforced the social inequalities of political participation. 7…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Interest in politics and occupation also play here a stronger role than in the first round. As suggested by Haute and colleagues ( 2021 ), the pandemic context may have reinforced the social inequalities of political participation. 7…”
Section: Resultsmentioning
confidence: 93%
“…This unprecedented event offers an interesting quasi-experimental setting for measuring the impact of an external shock such as the global public health crisis and its political communication challenges on voting behaviour. Recent and preliminary studies have started using this opportunity and have shown that the pandemic caused either a rally round-the-flag effect, with massive electoral support for incumbents, or massive abstention (Brouard and McAvay 2020 ; Haute et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The latest global phenomenon that the entire world population has been experiencing, that is COVID-19 totally fulfils all the characteristics of a socially relevant topic as it brings profound social consequences due to several factors, for example, mass quarantine (Chu et al, 2020), it (a) concerns different social institutions from the police (Frenkel et al, 2021) to families (Thomeer et al, 2020), it (b) touches on a diverse set of social categories from migrants (Knights et al, 2021) to the elderly (da Rocha et al, 2021), it (c) impacts elections in several countries (Haute et al, 2021;James, 2021), it (d) feeds the hotbed of discussion on a wide range of contemporary issues from euthanasia (Salinas Mengual, 2021) to environmental concerns (Sarkodie and Owusu, 2021) and (e) beyond being considered a pandemic phenomenon comparable to HIV (already considered by the literature as socially relevant) in terms of social weight, it is also considered to affect the spread of HIV because of prolonged lockdowns in countries with high HIV rates (Dorward et al, 2021). Finally (f) COVID-19 has been a cross-cutting phenomenon studied with unmatched intensity across different academic domains (Else, 2020).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Ces élections ont été marquées par une très faible participation dans la région : 32,84 % au premier tour et 33,18 % au second tour contre respectivement 54,81 % et 61,24 % lors du précédent scrutin, en décembre 2015. Alors que le scrutin s'est tenu en pleine crise liée à la Covid-19, cette démobilisation électorale, observé dans le reste du pays, mais encore plus importante dans les Hauts-de-France, n'a néanmoins pas été directement liée au risque sanitaire. Il n'y a ainsi pas eu, en juin 2021, de démobilisation plus importante des personnes âgées les plus à risque par rapport aux autres électeurs (Haute 2021), -contrairement à ce qui avait été observé lors des élections municipales de 2020 (Haute et al, 2021) -, ou encore des personnes non vaccinées ou hostiles à la vaccination. Si l'adhésion vaccinale est allée de pair avec une participation plus importante ( Jaffré 2021), ce résultat se vérifiait déjà pour de précédents scrutins (Ward et al 2020).…”
unclassified